Do polymorphic variants of chromosomes affect the outcome of in vitro fertilization and embryo transfer treatment? - Hong, Y. (Oxford University Press, 2011)
BACKGROUND: The aim of this study was to investigate the effect of chromosomal polymorphic variations on the outcome of IVF and embryo transfer (IVF–embryo transfer) treatment for infertile couples. METHODS: During the period from October 2006 to December 2009, 1978 infertile couples who had received their first IVF–embryo transfer treatment cycle in our hospital were selected for this retrospective study, and the frequency of chromosomal polymorphic variations was calculated. From these, 1671 couples were selected and divided into three groups: 1402 couples with normal chromosomes (Group 1/control group), 82 couples with chromosomal polymorphic variations in only females (Group 2) and 187 couples with chromosomal polymorphic variations in only males (Group 3). The clinical pregnancy rates (CPR), early miscarriage rates and ongoing pregnancy rates after IVF–embryo transfer treatment were compared. RESULTS: There were no statistically significant differences among the three groups in implantation rates (29.37% in the control group, 29.70% in Group 2 and 31.41% in Group 3, P > 0.05) and CPR (45.86, 46.34 and 51.87%, respectively, P > 0.05). Although there was a trend toward higher first trimester pregnancy loss rates in Group 3 (male chromosomal polymorphic variations), but not in Group 2, compared with normal karyotype couples (10.31 versus 6.84%), the difference did not reach significance (P > 0.05). CONCLUSIONS: Chromosomal polymorphic variations appear to have no adverse effects on the outcome of IVF–embryo transfer treatment.